Validation of black spot [(Pseudocercospora purpurea (Cooke) Deighton] management strategies in avocado crops in northern Tolima (Colombia) - Rodríguez-Polanco, Eleonora; Reina-Noreña, Julian Alberto; Tamayo-Molano, Pablo Julian; Rodríguez-Polanco, Luz Astrid; Varón-Devia, Edgar Herney (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
Leaf spot or black spot (BS) in avocado, caused by the fungus Pseudocercospora purpurea (Cooke) Deighton, is one of the main sanitary limitations for the production of avocado, particularly for the Antillean cultivars (Lorena, Choquette, Santana, and Semil 44) in the northern region of the department of Tolima, Colombia. During 2014-2017, different experiments were carried out in the field, aiming to determine the period of higher fruit susceptibility, the effect of pruning on inoculum reduction, and chemical molecules with a high degree of control, adjusting their chronology and frequency of application. The results allow the technical, economic, and environmental implementation and validation of a chemical strategy for management of this disease. The management strategy carried out by Agrosavia reported a 10% lower incidence of BS in fruits, compared to the one carried out by producers, and a 23.75% return, due to the increase in high quality fruits. In the latter, DMI fungicides (demethylation inhibitors), even without resistance reports, and fungicides with a mixture of two active ingredients (DMI and QoI) in interspersed application and sometimes in conjunction with CuOCl during periods of higher susceptibility to BS were used, aiming to reduce the resistance induction risk in P. purpurea.